PEMBANGUNAN LINGKUNGAN BERKELANJUTAN DAN PEMBERDAYAAN EKONOMI LOKAL MELALUI PROGRAM PENANAMAN 1000 POHON KETAPANG KENCANA DI DESA JENETALLASA, GOWA - Rosanti, Novita; Muspa, Muspa; Sujatmiko, Sujatmiko; Panus, Panus; Asrul, Asrul (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service program aims to promote a sustainable environment and empower the local economy through the planting of Ketapang Kencana trees in Jenetallasa Village, Gowa. The program was implemented in August 2025 over a period of two weeks, engaging the community in all stages, including land survey, seedling preparation, tree planting, maintenance, and utilization of tree-derived products. Technical training was provided to enhance the community’s skills in seedling propagation, planting, tree care, and processing leaves and seeds into economic products. Results showed optimal tree growth, high community participation, and significant improvement in local residents’ skills. Utilization of tree-derived products opened local economic opportunities through compost, handicrafts, tree seedlings, and agro-tourism education. The program fostered a sense of ownership among the community toward their environment, encouraging sustainable reforestation. These findings demonstrate that integrating sustainable reforestation and local economic empowerment can be effectively implemented with proper technical training, active community engagement, and systematic management of tree-derived products, and the model has potential to be replicated in other villages.